Enantioselective addition of diphenyl phosphonate to ketimines derived from isatins catalyzed by binaphthyl-modified organocatalysts - Jang, Hee Seung; Kim, Yubin; Kim, Dae Young (Beilstein Journal of Organic Chemistry, 2016)
Chiral binaphthyl-modified squaramide-catalyzed enantioselective addition of diphenyl phosphonate to ketimines derived from isatins has been achieved. This method affords practical and efficient access to chiral 3-amino-3-phosphonyl-substituted oxindole derivatives in high yields with excellent enantioselectivities (up to 99% ee).
Keywords: 3-amino-3-phosphonyl-substituted oxindole; α-aminophosphonates; bifunctional organocatalyst; ketimines; organocatalysis; squaramide